Answer:
H(s)=(∫_(t=o)^∞▒〖x(t)e^(-st) dt〗)/(∫_(t=o)^∞▒〖y(t) e^(-st) dt〗)
Step-by-step explanation:
L{f(t)}=F(s)=∫_(t=0)^∞▒〖f(t)e^(-st) dt〗
Answer:
Step-by-step explanation:
(12-3)/2 = 9/2
(-5-3)/2= -8/2= -4
(9/2, -4)
Answer:
69.94 miles
Step-by-step explanation:
The distance d₁ the first ship moves after 3 hours is 3 hours × 15 miles per hours = 45 miles
The distance d₂ the second ship moves after 3 hours is 3 hours × 12 miles per hours = 36 miles.
The angle the first ship's direction makes in the North-East direction is 90° - 75° = 15°
The angle the second ship's direction makes in the South-West direction = 14°
The distance moved by the two ships form the side of a triangle. The angle, θ between the two ship directions is 14° + 90° + 15° = 119°
Using the cosine rule, we find the distance d between the two ships
d = √(d₁² + d₂² -2d₁d₂cosθ)
= √(45² + 36² -2×45×36cos119°)
= √(2025 + 1296- (-1570.78))
= √(3321 + 1570.78)
= √4891.78
= 69.94 miles
Let
a------------> first number
b------------> second number
we know that
a+b=-7--------> a=-7-b----------> equation 1
a-b=14--------> equation 2
<span>I substitute 1 in 2
</span>
(-7-b)-b=14-------------> -7-b-b=14----------> -7-2b=14-------> 2b=-7-14
2b=-21---------> b=-10.5
a=-7-b-------> a=-7-(-10.5)-----> a=-7+10.5------> a=3.5
the answer is
the two numbers are
a=3.5
and
b=-10.5